The precise and accurate dating of medieval bridge remains at Ancrum, Scottish Borders, using stable isotope dendrochronology - Darren Davies (Journal of Archaeological Science: Reports, 2024)
The discovery of Ancrum Old Bridge (River Teviot, Scotland) in 2018 was a significant archaeological finding for Scotland. Wiggle match radiocarbon dating placed construction of the bridge to around 1340–1360 Cal. AD (95.4 %); a period of political and social instability in the region. Oxygen isotope dendrochronology was applied to refine this date range and to provide a precise felling date for the bridge timbers. Somewhat unexpectedly, a felling date of winter AD 1428/29 was identified. This date was obtained using a reference chronology for the southern United Kingdom and independently verified against a new local isotope chronology developed from native Scottish oak. This new date falls within a more stable period in Scotland’s history which may have been more suited to major construction projects such as Ancrum Old Bridge. These results highlight the importance for radiocarbon end users to consider the nature of dating uncertainty when interpreting results, especially when the probability distribution is multi-modal.